Implementation of Clinical Supervision to Increase Work Commitment of Primary School Teachers - Kusumawati, Gusti Ayu (Universitas Pendidikan Ganesha, 2020)
The purpose of this study was to determine the increase in elementary school teacher work commitments in Gugus 3 Kecamatan Blahbatuh Kabupaten Gianyar Semester II Academic Year 2018/2019 after attending clinical supervision activities. This research is a school action research. Subjects were elementary school teachers in Gugus 3 Kecamatan Blahbatuh Kabupaten Gianyar with a total of 58 teachers. Teacher work commitment data in this study were collected using a questionnaire. Data analysis techniques used descriptive analysis. Indicators of the success of this study are: if the minimum teacher work commitment is in the High category and classical completeness is 90%. Based on the research that has been done, it was concluded that the effective implementation of clinical supervision could increase the work commitments of elementary school teachers in Cluster 3 of Blahbatuh District, Gianyar Regency Semester II in 2018/2019 Academic Year. In the pre-cycle mean teacher work commitment is 128.74 in the medium category with the percentage of classical completeness is 67.24%. In the first cycle the mean work commitment of teachers was 145.98 in the high category with the percentage of classical completeness being 87.93%. Whereas, in cycle II it increased with a mean of 180.45 in the very high category with the percentage of classical completeness being 100%.